Bookshelf: Kappan authors on their favorite reads. (May 2021) - Kim, Robert
In this monthly column, Kappan authors discuss books and articles that have informed their views on education. Robert Kim recommends Minor Feelings: An Asian American Reckoning by Cathy Park Hong, Sarah Pazer recommends the multi-author Manifesto for Teaching Online, and Thomas Hatch recommends Tinkering Toward Utopia: A Century of Public School Reform by David Tyack and Larry Cuban .